The Influence of Transformational Leadership and Motivation on Employee Performance at Anugerah Palembang Hotel - Agung Wijaya; Muhammad Wadud; M. Kurniawan DP (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the effect of transformational leadership and motivation on employee performance at Anugerah Palembang Hotel. The number of samples in this study were 35 respondents. The data collection technique utilizedquestionnaires. The data analysis technique utilized multiple linear regression analysis. This study finds that transformational leadership and motivation have a significant effect on employee performance partially and simultaneously. The results of this study are expected to provide benefits for Hotel Anugerah Palembang to improve employee performance through transformational leadership and motivation.